Clinical experience: Outcomes of mesenchymal stem cell transplantation in five stroke patients - Ercelen, Nesrin; Karasu, Nilgun; Kahyaoglu, Bulent; Cerezci, Onder; Akduman, Rana Cagla; Ercelen, Defne; Erturk, Gizem; Gulay, Gokay; Alpaydin, Nagihan; Boyraz, Gizem; Monteleone, Berrin; Kural, Zekiye; et al. (Frontiers in Medicine, 2023)
Stem cell therapy, which has promising results in acute disorders such as stroke, supports treatment by providing rehabilitation in the chronic stage patients. In acute stroke, thrombolytic medical treatment protocols are clearly defined in neurologic emergencies, but in neurologic patients who miss the “thrombolytic treatment intervention window,” or in cases of hypoxic-ischemic encephalopathy, our hands are tied, and we are still unfortunately faced with hopeless clinical implementations. We consider mesenchymal stem cell therapy a viable option in these cases. In recent years, novel research has focused on neuro-stimulants and supportive and combined therapies for stroke. Currently, available treatment options are limited, and only certain patients are eligible for acute treatment. In the scope of our experience, five stroke patients were evaluated in this study, who was treated with a single dose of 1–2 × 106 cells/kg allogenic umbilical cord-mesenchymal stem cells (UC-MSCs) with the official confirmation of the Turkish Ministry of Health Stem Cell Commission. The patients were followed up for 12 months, and clinical outcomes are recorded. NIH Stroke Scale/Scores (NIHSS) decreased significantly (p = 0.0310), and the Rivermead Assessment Scale (RMA) increased significantly (p = 0.0234) for all patients at the end of the follow-up. All the patients were followed up for 1 year within a rehabilitation program. Major clinical outcome improvements were observed in the overall clinical conditions of the UC-MSC treatment patients. We observed improvement in the patients’ upper extremity and muscle strength, spasticity, and fine motor functions. Considering recent studies in the literature together with our results, allogenic stem cell therapies are introduced as promising novel therapies in terms of their encouraging effects on physiological motor outcomes.